THE HISTORICAL PATH OF FORENSIC MEDICINE: FROM LAW TO MEDICINE, FROM MEDICINE TO HIGH TECHNOLOGY - Irina L. Levina; Leonid N. Korol (Russian Studies in Law and Politics)
In the structure of the discipline (module) “Forensic Medicine and forensic psychiatry” for students majoring in 40.05.02 – law enforcement, very little time is devoted to the history of forensic medicine, which at all stages of its development is closely connected with the history of law and the development of the world judicial and legal system. Forensic medicine originated, developed and took shape in the process of administrative and judicial practice involving competent persons in the investigation and consideration of criminal and civil cases to clarify issues requiring special medical knowledge. The purpose of the work is to show the origins and historical stages of the development of forensic medicine in accordance with the formation of the state legal system in the world and in our country. The paper presents the origins of forensic science, the main stages of its formation and shows the prospects for further development. Traditions and modern development of world forensic medicine are closely connected with the development of law and the world state-legal system. Knowledge of the stages of the formation of forensic medicine allows you to better understand the history of legal science, legal proceedings and public administration.